What is the métier of ethnobiology or why should this science be busy? - Albuquerque, Ulysses Paulino (Ethnobotany Research and Applications, 2022)
Ethnobiologists have been guiding their research from different approaches and disciplinary lenses. There are those who defend a scientifically-oriented ethnobiology while others believe in an engaged ethnobiology (or an ethnobiology of action) aimed at learning from ancestral wisdom and, simultaneously, supporting the holders of this wisdom in different demands. But what then would be the job of ethnobiologists? From a narrative, briefly centered on our academic trajectory, I argue how ethnobiology can constitute an epistemological umbrella under which there would be space for epistemic and theoretical diversities.